Sistem Informasi Pemesanan Jasa Dekorasi Pernikahan Berbasis Web Di Echy Salon - Siti Hadiyah (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2023)
Echy Salon Wedding Organaizer is a wedding service in the city of Ternate that provides several wedding packages whose orders are still manually. This causes the problem that the bride and groom often cannot meet the owner because they are not in place so that the bride and groom must come directly to the Echy Salon Wedding Organaizer to place an order or just find out information on the services provided at the wedding organizer, confirmation of payment still has to come to the place. . With the whole process causing some problems in time efficiency and difficulty in booking wedding packages. To overcome this problem, an online wedding package ordering information system was built. The system uses the waterfall method. This system uses blackbox testing to find out whether the data entered is correct or not and how the output results are in line with expectations or not. Keywords: Information System, Wedding Organaizer, Web